ANALYSIS OF ASSETS AND LIABILITIES RECOGNITION RELATED TO TAX AMNESTY PROGRAM: COMPARATIVE OF ACCOUNTING AND TAX REGULATIONS - Adang Hendrawan; Muthia Khairunnisa Hapsari; Milla Sepliana Setyowati (International Journal of Accounting, Finance and Business, 2018)
This research analyzed the regulations of additional asset and liability recognition based on tax amnesty program determined in Indonesia’s Tax Amnesty Law and Declaration of Financial Accounting Standard (DFAS) No. 70 on Asset and Liabilities Accounting of Tax Amnesty.The analysis referred to argumentation about tax conception of regulator and the financial position of the tax amnesty’s asset and liability. This study used qualitative approach to get a clearer understanding about the difference between tax and accounting policy in regulating the tax amnesty’s asset and liability recognition along with the impacts. This study showed that the difference between tax and accounting policy was located in choosing the appropriate account under the equity balance. According to the tax regulation, the account stated as Retained Earnings. Meanwhile, the accounting Standard stated the account as Paid in Capital. The difference gave some impacts to taxpayer that was analyzed from psychological cost and certainty principle.